Whole Exome Sequencing and Segregation Analysis Confirms That a Mutation in COL17A1 Is the Cause of Epithelial Recurrent Erosion Dystrophy in a Large Dominant Pedigree Previously Mapped to Chromosome 10q23-q24. - Benjamin R Lin; Derek J Le; Yabin Chen; Qiwei Wang; D Doug Chung; Ricardo F Frausto; Christopher Croasdale; Richard W Yee; Fielding J Hejtmancik; Anthony J Aldave (PLoS ONE)
Purpose To report identification of a COL17A1 mutation in a family with a corneal dystrophy previously mapped to chromosome 10q23-q24. Methods Whole-exome sequencing was performed on DNA samples from five affected family members and two unrelated, unaffected individuals. Identified variants were filtered for those that were: located in the linked interval on chromosome 10q23-q24; novel or rare (minor allele frequency ≤0.01); heterozygous; present in all affected individuals and not in controls; and present in genes that encode proteins expressed in human corneal epithelial cells (reads per kilobase per million ≥1). Sanger sequencing of identified variants (SNVs) was performed in additional family members. In silico analysis was used to predict the functional impact of non-synonymous variants. Results Three SNVs located in two genes were identified that met the filtering criteria: one rare synonymous c.3156C>T variant in the collagen, type XVII, alpha I (COL17A1) gene; and two rare variants, one synonymous and one missense, in the dynamin binding protein (DNMBP) gene. Sanger sequencing of additional family members determined that only the COL17A1 variant segregates with the affected phenotype. In silico analysis predicts that the missense variant in DNMBP would be tolerated. Conclusions The corneal dystrophy mapped to chromosome 10q23-q24 is associated with the c.3156C>T variant in COL17A1. As this variant has recently been identified in five other families with early onset recurrent corneal erosions, and has been shown in vitro to introduce a cryptic splice donor site, this dystrophy is likely caused by aberrant splicing of COL17A1 and should be classified as epithelial recurrent erosion dystrophy.